الاختيارات الفقهية للشيخ عبد الله البسام (رحمه الله) في كتاب الزكاة والصيام - النفيعي، بندر مهدي; حمدان، عبدالمطلب عبدالرزاق إبراهيم (الطائف, 2012)
Praise be to Allah the Lord of the Worlds, Peace and Blessing upon the Noblest Prophets and Messengers our Master Mohammad and all of his family and his Companions. This thesis is about choices of Sheikh Abdullah AlBassam (May Allah bless him) in his books Zakah(Alms)and Fasting as follow: 1- Introduction, consist as follow: • The important of the subject • The reasons for selecting the topic • Research methodology • Research plan 2- The preface consist of Sheikh Abdullah AlBassam biography as follow: • His Lineage , surname , born , grew up , seeking knowledge , Senates , students, Jobs , work , publications , Activities in calling to Allah and the scientific method which he followed and his death. 3- Two researches as follow: • First research: choices of Sheikh AlBassam in Zakah (Alms)book. Consist of three chapters: First chapter: Zakat Al Amwal (money) acceleration or delay it and obligatory placements. Second chapter: Channels of spending Zakah(alms). Third chapter: fast- breaking Zakah(alms) The amount and how to disburse it to the beneficiaries. • Second research choices of Sheikh AlBassam in fasting book consist of three chapters: First chapter: Evidence of Ramadan and it's conditions. Second chapter: What invalidate and does not invalidate fasting. Third chapter: fasting authorization and other 4- The conclusion I mentioned the important results that came through out of the research. Asking Allah to guide me toward the right path and teach me what is good for me. Peace and blessing of Allah be upon our prophet Mohammed
Keywords: الاختيارات الفقهية -- البسام،عبد الله -- الزكاة -- الصيام -- الفقه الإسلامي